Whatever happened to compassionate Conservatism under the Coalition government?. Issue 2 (12th June 2018) - Bochel, Hugh; Powell, Martin
Abstract Following David Cameron's election as leader of the Conservative Party in late 2005, a series of initiatives suggested that he was seeking to reposition the Conservative Party, or perhaps to introduce some new thinking to the Party and to align it with interests and issues that it had not been linked with since at least the start of the Thatcher period. At the time, views among commentators varied about whether this was a genuine attempt to change the Conservative Party, including through a more compassionate approach to some social groups and problems, or whether it was simply designed to 'detoxify' the Party and to make it electable once more. However, many observers were unconvinced that the five years of the Coalition government saw significant evidence of the 'compassionate' ideas that Cameron and others sought to highlight prior to the 2010 general election. This article explores a number of possible reasons for the apparent disappearance of compassionate Conservatism in relation to social policies under the Coalition government. It suggests that rather than any one explanation, drawing upon a number of interpretations may provide the best understanding of the role and impact of compassionate Conservative ideas from 2010 to 2015.